The Role of Sechium edule Fruits Ethanolic Extract in Insulin Production and Malondialdehyde Level in Stz-Induced Diabetic Rat - Betty Lukiati; Nugrahaningsih Nugrahaningsih; Siti Nur Arifah (Journal of Tropical Biodiversity and Biotechnology, 2019)
The objectives of this research were to examine the effect of Sechium edule ethanolic extract in insulin and Malondialdehyde (MDA) levels in streptozotocin (STZ) induced diabetic rats. Type 1 diabetic rat were obtained by intraperitonially injected with multiple low dose STZ (MLD-STZ) 20 mg/kgBW for 5 days. The animals were divided into 5 groups: untreated rats in group (K) were considered as negative control, MLD-STZ induced type 1 diabetic rats in group (S) were considered as positive control. In another 3 group (A, B, C) type 1 diabetic rats were orally treated with three doses of S. edule ethanolic extract (14, 28, 42 mg/kg BW) for 7 days. The animals were sacrificed in two days after last treatment, serum were collected for measuring of the insulin concentration by ELISA method. Level of MDA on kidney, liver and pancreas were measured by TBA method. The treatment with S. edule ethanolic extracts unable to increase of insulin yet but the treatment with 42 mg/kg BW of S. edule ethanolic extract showed significantly decreased MDA levels on liver but not significant on kidney and pancreas.